Pendampingan Pembuatan Alat Pengukur Kesuburan Tanah (pH) di Desa Rejosopinggir Kecamatan Tembelang Kabupaten Jombang - Khotim Fadhli; Canggih Nailil Maghfiroh; Lailatus Saadah; Achmad Miftahul Huda; Muhamad Iin Pranata; Zahrotun Nisak; Mohamad Nasirudin (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2022)
The community service carried out aims to train the community on the application of appropriate technology for measuring soil fertility (pH). Service activities in Rejoso Hamlet, Rejosopinggir Village, Tembelang District, Jombang Regency, East Java. The implementation of community service activities will be carried out in November 2021. The implementation method for implementing community service activities in the Participatory Action Research method. The action and participatory method was carried out in the socialization of the use of soil fertility (pH) measuring devices. Community service, the application of appropriate technology for soil fertility (pH) testing equipment, has several benefits, including being able to make it easier to predict soil fertility on agricultural land, increasing fertilization efficiency, increasing the ability and independence of farmers. The socio-economic conditions of the community have undergone many changes in the fertilization process because fertilization is aimed only at less fertile land. Balanced fertilization and as needed will improve the quality of the soil chemically so that it is more optimal for plant growth. Fertilization efficiency can be achieved so that it will reduce farmer's capital and potentially increase farm income. Farmers are also given the opportunity to develop themselves and utilize used goods into appropriate technological tools. Keywords : soil fertility, pH, appropriate technology, community service